Stomatal Response of Populus Clones to Light Intensity and Vapor Pressure Deficit - Pallardy, Stephen G. (1979)
Responses of stomata of clones of Populus candicans Ait. × P. berolinensis Dipp. and Populus deltoides Bartr. × P. caudina (Ten.) Bugala to two levels of light intensity and vapor pressure deficit were studied in controlled environments. Significant stomatal responses to light and vapor pressure deficit were observed. Interactive effects of low light intensity and high vapor pressure deficit elicited greater stomatal closure than was obtained under low light or high vapor pressure deficit alone, indicating adaptation for increased water use efficiency under conditions unfavorable for photosynthesis relative to transpiration. Adaxial stomata of both clones were more sensitive than abaxial stomata to changing vapor pressure deficit and light intensity. Stomatal response to vapor pressure deficit appeared to be independent of bulk leaf water status. Stomata of P. candicans × P. berolinensis were more sensitive than stomata of P. deltoides × P. caudina to a change in vapor pressure deficit and less sensitive to a change in light intensity. The sensitivity of stomata of P. candicans × P. berolinensis to vapor pressure deficit may be related to drought resistance in its parentage (P. berolinensis).